The Effect of Strategic Management and Principal’s Competency on Teacher’s Teaching Quality - Amaliah, Amaliah; Fitria, Happy; Rohana, Rohana (Yayasan Sembilan Pemuda Indonesia, 2024)
The low quality of education in Indonesia is caused by the low competence of educators. To improve the teaching and learning process, teachers must be responsible and accountable. The school principal’s strategic management values can also contribute to educational improvement. The principal’s role includes planning, organizing, mobilizing, and evaluating resources to achieve the school’s vision, mission, and goals. The researchers’ study regarding the influence of strategic management and principal competence on the quality of teaching at SMPIT in Prabumulih City is quite interesting. This research examines the impact of principal strategic management, principal competence, and teacher teaching quality at Prabumulih City SMPIT schools, specifically SMPIT Ishlahul Ummah and SMPIT Al Hasanah. The study uses a census sample of 53 teachers, utilizing questionnaires, observation, and documentation methods to gather data. The research reveals that strategic management significantly influences the teaching quality of teachers at SMPIT in Prabumulih City, while the school principal’s competency significantly impacts the teaching quality. The combined effect of these two factors is 78%, with 22% influenced by other variables.